A Simple Techno-Economic Assessment for Scaling-Up the Enzymatic Hydrolysis of MSW Pulp - Climent Barba, Fernando; Grasham, Olivier; Puri, Dhivya J.; Blacker, A. John (Frontiers in Energy Research, 2022)
A techno-economic assessment (TEA) of enzymatic hydrolyses of a municipal solid waste (MSW)-derived pulp was performed to compare various bioprocessing configurations for the production of platform sugars at both pilot and demonstration scales (two-stage continuous, batch, and two-stage fed-batch). The configurations modeled used either rotary drum and/or continuous stirred tank reactors. By using reaction kinetics and public vendor’s quotes, economic analyses were calculated for each of the proposed systems: capital expenditure (CapEx); operation expenditure (OpEx); revenue and profit; return on investment (ROI); and payback period (PP). The TEA showed that a two-stage continuous configuration with a total residence time of 54 h (6 and 48 h for primary and secondary stages) was the best option for obtaining sugars, showing sevenfold higher enzyme productivity and better profit than the reference systems. Although pilot-scale enzymatic hydrolysis demonstrated an unprofitable process, this was mainly due to the high associated enzyme cost. Increasing the scale diminished this problem, leading to higher profit per processed unit (£/kg lignocellulosic sugars). From an investment perspective, the two-stage 6/48 configuration gave a more attractive ROI and PP than the other designs.